Literature Review: Physical Education Learning, Emotional Intelligence as a Predictor of 21st Century Skills Domain - Fegie Rizkia Mulyana; Bogy Restu Ilahi; Defri Mulyana; Aang Rohyana; Pepep Mochamad Syafei; Andes Permadi; Ari Sutisyana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
Challenges in the era of disruption require individuals to possess not only intellectual intelligence but also emotional intelligence to navigate problems and challenges effectively. Emotionally intelligent individuals can handle difficulties in learning processes and manage stress when facing real-life problems. Physical Education serves as a medium to develop students' social and emotional skills through its curriculum. This review aims to understand how Physical Education in Indonesia contributes to the development of students' emotional intelligence over the past ten years. The study employs a literature review method, collecting articles through search engines such as Google Scholar. The selection criteria include articles published from 2013 to 2022. The findings indicate a positive correlation between Physical Education and emotional intelligence in developing essential 21st-century skills. This study emphasizes that emotional intelligence can be fostered through affective learning in Physical Education, explicitly designed to build students' character and emotional intelligence in facing 21st-century challenges. Furthermore, emotional intelligence predicts students' ability to develop 21st-century skills, such as teamwork, effective communication, problem-solving, and creative thinking.